2019
DOI: 10.1177/0269215519845034
|View full text |Cite
|
Sign up to set email alerts
|

A study of whether individual and dyadic relations between spirituality and resilience contribute to psychological adjustment among individuals with spinal cord injuries and their family members

Abstract: Objective: To test a model of spiritual well-being and resilience among individuals with spinal cord injuries and their family members. Design: Prospective cross-sectional observational data were analyzed by structural equation modelling. Setting: Inpatient and community services at one rehabilitation hospital. Subjects: Individual with spinal cord injury ( n = 50) and family member ( n = 50) dyads. Interventions: Standard rehabilitation, both inpatient and community. Main measure(s): Functional assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…In terms of the quantitative observational studies, the one finding of note was a weak positive association between spirituality and depression (Qiu & Li, 2018), and the authors speculated that this link might indicate that religion was a temporary escape mechanism but without providing long-term relief from the stresses of caregiving. However, observational studies among caregivers with SCI and TBI have found the opposite, with spirituality acting as a buffer or protective factor, either in direct association with depression (Simpson et al, 2020) or as mediated through resilience (Jones, Simpson, Briggs et al, 2019). So further research will be required to help clarify this issue among caregivers of people with stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the quantitative observational studies, the one finding of note was a weak positive association between spirituality and depression (Qiu & Li, 2018), and the authors speculated that this link might indicate that religion was a temporary escape mechanism but without providing long-term relief from the stresses of caregiving. However, observational studies among caregivers with SCI and TBI have found the opposite, with spirituality acting as a buffer or protective factor, either in direct association with depression (Simpson et al, 2020) or as mediated through resilience (Jones, Simpson, Briggs et al, 2019). So further research will be required to help clarify this issue among caregivers of people with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…At a theoretical level, Smith and colleagues (2012) have asserted that healthy spirituality can contribute to better health out-comes, and this is supported by reviews of patient studies across the general health literature (Koenig, 2012). In the field of neurologic insult, initial studies that investigated the applicability of this research to the lives of family caregivers (after spinal cord injury (SCI) or traumatic brain injury (TBI)), found that spirituality had a protective (inverse) association to negative affect, depression and burden, and a positive association with positive affect (Jones et al, 2019;Simpson et al, 2020). These results reflect findings from studies among people with SCI or TBI which have found a positive association between spirituality and better life satisfaction, quality of life, and positive mental health (Jones et al, 2016;Jones et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Re-affirming relationship strength was found to mutually benefit both the individual with SCI, and the social support, founded by the ‘deepening of relationships’ (Jones et al, 2018 , p. 527). However, this finding is inconclusive as a later study by Jones, Simpson, Briggs, Dorsett, and Anderson ( 2019 ) found that no intercorrelation exists between spirituality and resilience of the individual with SCI, and their social supports. While an explanation for the lack of mutual dyadic benefits is not given, the authors note that this finding is inconsistent with similar studies employing qualitative methods (Jones et al, 2019 ).…”
mentioning
confidence: 92%
“…However, this finding is inconclusive as a later study by Jones, Simpson, Briggs, Dorsett, and Anderson ( 2019 ) found that no intercorrelation exists between spirituality and resilience of the individual with SCI, and their social supports. While an explanation for the lack of mutual dyadic benefits is not given, the authors note that this finding is inconsistent with similar studies employing qualitative methods (Jones et al, 2019 ). Spirituality, as an inconclusive psychosocial contributor of resilience warrants further empirical examination.…”
mentioning
confidence: 92%